Perspektywy rozwoju ochotniczych straży pożarnych - Konieczny, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Voluntary fire brigade units have been functioning for more than 70 years and have played a very important role in public safety system which since 1995 has been included in national firefighting and rescue system KSRG.In Lower Silesia within the years of national firefighting and rescue system’s functioning the number of units of voluntary fire brigade subordinate to the system has doubled and the growing number of companions in operational and technical units is a sign of its mass scale. Nevertheless, it also indicates the organizational, financial and system responibilities of government and local government administration which need to be introduced in order to take advantage of such a great and numerous potential.The article highlights the fundamental and most significant problems concerning voluntary fire brigade which have occurred in the area of Lower Silesia within the last two years focusing on tasks to be done.
Keywords: bezpieczeństwo publiczne; ryzyko; administracja; samorząd; straż pożarna; współpraca